2003
DOI: 10.1542/peds.112.3.506
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computerized Physician Order Entry on Medication Errors and Adverse Drug Events in Pediatric Inpatients

Abstract: The introduction of a commercially available physician computer order entry system was associated with a significant decrease in the rate of medication errors but not ADEs in an inpatient pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
157
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(164 citation statements)
references
References 22 publications
4
157
1
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] There can be unintended consequences as well, however, [15][16][17][18][19][20][21][22][23][24] and it is likely that fear of adverse unintended consequences is impeding the diffusion of CPOE throughout hospitals in the U.S. [25][26][27][28][29] The unintended consequences of CPOE are especially intriguing because they can surprise implementers. Adverse unintended consequences unfortunately can become impediments to health care quality.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] There can be unintended consequences as well, however, [15][16][17][18][19][20][21][22][23][24] and it is likely that fear of adverse unintended consequences is impeding the diffusion of CPOE throughout hospitals in the U.S. [25][26][27][28][29] The unintended consequences of CPOE are especially intriguing because they can surprise implementers. Adverse unintended consequences unfortunately can become impediments to health care quality.…”
Section: Introductionmentioning
confidence: 99%
“…King et al (2003) reported that the adoption of computerized prescriber order entry (CPOE), a crucial component of EMRs, decreased medication errors by 40%. Additionally, Bates et al (2001) found that EMR adoption reduced absolute adverse drug events by 70%.…”
Section: Introductionmentioning
confidence: 99%
“…HIS may also improve health care quality through the use of standardized clinical pathways; e-prescribing systems, which would detect drug interactions; and better and more complete documentation of care [14]. These improved processes are expected to lead to significant reductions in medical errors [20][21]. The automated access of physicians to patient laboratory and other diagnostic results may reduce lost orders and errors due to illegible handwriting, and minimize duplicate orders [22], thus improving health care quality outcomes and efficiency [23].…”
Section: Review Of Literature 21 Hismentioning
confidence: 99%